2012
DOI: 10.1002/met.1314
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and prediction of helicopter‐triggered lightning over the North Sea

Abstract: Helicopter-triggered lightning is a phenomenon which affects operations over the North Sea during the winter. It is thought that the presence of the helicopter triggers the majority of lightning strikes, since there is generally little or no natural lightning activity in the area in question prior to or following the strike, and strike rates are much higher than would be expected if due purely to chance. However, there has been little progress to date in the ability to predict triggered lightning strike occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Gough et al (2009) identified that 40 % of the studied lightning events involving airplanes occurred during the "cold season", which is not the period of the most frequent thunderstorm activity. Moreover, Wilkinson et al (2013) concluded that because the lightning strike rate to helicopters in the North Sea during winter was much higher than expected, the presence of a helicopter actually triggers lightning. This phenomena presents a significant safety risk to helicopters doing operations under these conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gough et al (2009) identified that 40 % of the studied lightning events involving airplanes occurred during the "cold season", which is not the period of the most frequent thunderstorm activity. Moreover, Wilkinson et al (2013) concluded that because the lightning strike rate to helicopters in the North Sea during winter was much higher than expected, the presence of a helicopter actually triggers lightning. This phenomena presents a significant safety risk to helicopters doing operations under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although globally lightning activity associated to winter thunderstorms is relatively low compared with summer thunderstorms, these storms can produce very energetic lightning events and a large amount of damage (e.g., Yokoyama et al, 2014). Moreover, winter storms present the most favorable conditions for the initiation of upward lightning flashes from sensitive tall structures such as wind turbines (e.g., Montanyà et al, 2014a) and for flying aircraft (e.g., Wilkinson et al, 2013). A recent study by Honjo (2015) of a sample of 506 lightning currents to wind turbines in Japan concludes that winter lightning currents tend to feature longer duration currents, often bipolar, and that some particular wind turbines can be struck by lightning repeatedly in short periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…This is relatively a low number when compared to the hundreds to thousands of lightning flashes per hour that occur in a warm season thunderstorm (Bech et al, 2013;Schultz & Vavrek, 2009). Thundersnow storms also have convective features, which can produce a large amount of snowfall accumulation in a short period of time (Crowe et al, 2006;Pettegrew et al, 2009) that may severely impact the environment, including transportation, aviation, risk of lightning flashes, and other unexpected hazards (Cherington, 2001;Mäkelä et al, 2013;Wilkinson et al, 2013). Thus, a good understanding of these kinds of weather events could help forecasters and warn the public of upcoming hazards.…”
Section: Introductionmentioning
confidence: 99%
“…From a regional perspective they tend to be multi‐day events that can bring snow to populated areas. Moreover, they are known to be associated with lightning that affects aviation safety (Wilkinson et al , 2013) and icing conditions that create hazards for marine vessels (Moore, 2013). They are a challenge to km‐scale models because the boundary layer is shallow, but the horizontal open‐ and closed‐cell mesoscale structures associated with the cold air outbreak can reach scales up to almost 100 km.…”
Section: Introductionmentioning
confidence: 99%